1994
DOI: 10.1128/jvi.68.7.4227-4240.1994
|View full text |Cite
|
Sign up to set email alerts
|

Simian virus 40 large T antigen host range domain functions in virion assembly

Abstract: The simian virus 40 (SV40) T antigen host range mutants d11066 and d11140 display a postreplicative block to plaque formation which suggests a novel role for T antigen late in the viral life cycle. The host range mutants d11066 and d11140 are able to grow in and plaque on BSC but not on CV1 monkey kidney cells, a normally permissive host. Previous work showed that in CV1 cells infected with d11066 and d11140, levels of viral DNA replication and of late capsid protein accumulation were only slightly reduced and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…SV40 host range virus defects have been reported at several distinct stages of the viral life cycle in restrictive cells, including early and late gene expression (22)(23)(24), DNA replication (18), and virion assembly and release (25). Here, we have shown that formation of viral replication centers is also severely impaired for SV40 host range mutants.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…SV40 host range virus defects have been reported at several distinct stages of the viral life cycle in restrictive cells, including early and late gene expression (22)(23)(24), DNA replication (18), and virion assembly and release (25). Here, we have shown that formation of viral replication centers is also severely impaired for SV40 host range mutants.…”
Section: Discussionmentioning
confidence: 55%
“…Host range (HR) mutants of SV40 with specific deletions in the C terminus of LT fail to replicate efficiently and do not form plaques in restrictive cell lines, such as African green monkey kidney CV-1P cells or the human osteosarcoma cell line U-2 OS (U2OS here) (18,21,22). Under restrictive conditions, host range mutant viruses exhibit impairment at multiple stages of the viral life cycle, including decreased early (LT) and late (VP1 and VP3) gene and protein expression (22)(23)(24), impaired viral DNA replication (18), and defective virion assembly (25). Additionally, host range SV40 mutants are defective for the adenovirus helper function and, unlike wild-type SV40, cannot support human adenovirus replication in monkey cells upon coinfection (20,26).…”
mentioning
confidence: 99%
“…In case of the first possibility, the 30S Rep-Cap complexes would implicate the involvement of Rep proteins and possibly of AAV DNA in the capsid assembly process. Recently the involvement of the simian virus 40 large T antigen in capsid assembly was demonstrated (35,36), and similar results were obtained for the polyomavirus middle T antigen (13)(14)(15). Although in these cases no direct association of the large or middle T antigen with the capsid protein oligomers has been demonstrated, it is tempting to speculate that AAV Rep proteins play a role in AAV capsid assembly.…”
Section: Downloaded Frommentioning
confidence: 64%
“…Thus the deletion of the carboxyl‐terminal domain of T antigen affects both viral capsid protein synthesis and, through its action on agnoprotein, the assembly and maturation of virions (Stacy et al, 1989). Direct evidence for a defect in virion assembly and maturation in the C‐terminal T‐antigen mutants has been provided by sucrose density gradient analysis of virus‐infected cell extracts (Spence and Pipas, 1994). Intercistronic complementation of these mutants could be achieved with mutants of SV40 that were defective in agnoprotein but produced wild‐type T‐antigen.…”
Section: Early Studies Of the Role Of Sv40 Agnoprotein In The Viral Lmentioning
confidence: 99%